Birds of paradise : a novel - Abu-Jaber, Diana (New York : W.W. Norton & Co., 2011)
After a five year absence, an eighteen-year-old runaway returns to her family in Miami to deal with the guilty secret that caused her to flee.
Keywords: Runaway teenagers -- Fiction; Teenage girls -- Fiction; Families -- Fiction; Parent and teenager -- Fiction; Brothers and sisters -- Fiction; Miami (Fla.) -- Fiction; Domestic fiction; Psychological fiction